2022
DOI: 10.3389/fnbot.2022.937452
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphic or non-anthropomorphic? Effects of biological sex in observation of actions in a digital human model and a gantry robot model

Abstract: Robots are ever more relevant for everyday life, such as healthcare or rehabilitation, as well as for modern industrial environment. One important issue in this context is the way we perceive robots and their actions. From our previous study, evidence exists that sex can affect the way people perceive certain robot's actions. In our fMRI study, we analyzed brain activations of female and male participants, while they observed anthropomorphic and robotic movements performed by a human or a robot model. While ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…They presented to the subjects video clips with the four different types of movements (robot model—anthropomorphic vs. robotic movements; human model—anthropomorphic vs. robotic movements) in an MRI environment and investigated the underlying brain activity related to the observation of the different movements. Abel et al (2022) were able to show that males and females use different processing pathways in the brain when processing the perception of robotic and anthropomorphic movements. Females showed activations of the left hemispheric primary and secondary visual areas while observing the robot model.…”
Section: Gender Influence On Perception Of Robotic Actionsmentioning
confidence: 99%
See 3 more Smart Citations
“…They presented to the subjects video clips with the four different types of movements (robot model—anthropomorphic vs. robotic movements; human model—anthropomorphic vs. robotic movements) in an MRI environment and investigated the underlying brain activity related to the observation of the different movements. Abel et al (2022) were able to show that males and females use different processing pathways in the brain when processing the perception of robotic and anthropomorphic movements. Females showed activations of the left hemispheric primary and secondary visual areas while observing the robot model.…”
Section: Gender Influence On Perception Of Robotic Actionsmentioning
confidence: 99%
“…Furthermore, in the field of human-robot interaction, there is a large debate on the role of sex differences in operators on the perception of robots. It is reported that females generally show more positive attitudes toward anthropomorphic robots ( Lee, 2008 ; Abel et al, 2020 , 2022 ). Males, on the other hand, have more positive attitudes toward classical robots ( Cameron et al, 2018 ).…”
Section: Gender Influence On Perception Of Robotic Actionsmentioning
confidence: 99%
See 2 more Smart Citations